MGMT promoter methylation data for “EpiDirect enables rapid bisulfite-free MGMT promoter methylation testing in IDH-wildtype glioblastoma with high agreement across established assays” - Németh, Attila; Justus Liebig University Giessen (My University, 2026)
Analyzed data related to the “EpiDirect enables rapid bisulfite-free MGMT promoter methylation testing in IDH-wildtype glioblastoma with high agreement across established assays” manuscript by Németh et al., 2026 The uploaded XLSX file (38 kB) contains analyzed data from MGMT promoter methylation studies using EpiDirect, MGMT-STP27, methylation-specific PCR (MSP), pyrosequencing and methylation-specific droplet digital PCR (MS-dPCR), as well as relevant information and statistical analyses.